(untitled) (Bangladesh Journal of Medical Biochemistry, 2017)
Serum lithium concentration is monitored to ensure patient’s compliance and to avoid intoxication and thus it is a prerequisite for an individual’s dose adjustment. An unavoidable error during lithium estimation in blood collected in ’red-top plastic vacutainer plus tube containing silica clot activator and silicone surfactant’ by ISE appeared as a reality for a standard laboratory like AFIP. The error could not be detected even by proven internal and external QC. This cross-sectional study was carried out at AFIP Chemical Pathology Department from May’ 2015 to July’2015 to find out the interference causing falsely elevated serum lithium concentration by ISE principle. Blood were collected from the 40 study subjects including 30 healthy volunteers, who never took Tab Lithium and 10 patients, who used to take Tab Lithium for bipolar mood disorder in both ’plain red-top plastic vacutainer tubes without additive’ as well as ’plain red-top plastic vacutainer plus tube containing silica clot activator and silicone surfactant’. Lithium concentrations were estimated in both types of tubes by Ion-Selective Electrode (ISE) principle employing world class, USA manufactured analyzer NOVA-4 as well as by colorimetric method using Dade Dimension, Siemens. Serum lithium concentrations were undetectable for the ’lithium-free normal volunteers’ in both types of tubes measured by colorimetry but in ISE principle it was undetectable when collected in plain test tube without additives but when collected in ’vacutainer plus tube containing silica clot activator and silicone surfactant’ and measured by ISE technique, the mean serum lithium concentration was found to be 1.78 ±0.40 mmol/l. Besides, mean serum lithium concentration of 10 individuals taking Tab Lithium had no statistically significant difference while measured by ISE or colorimetry in ’vacutainer tubes without additive’ and also in ’vacutainer plus tubes containing silica clot activator and silicone surfactant’ measured by colorimetry. But, vacutainer plus tubes containing silica clot activator and silicone surfactant’ while measured serum lithium concentration by ISE principle had significant (p <0.001) increase in mean concentration than others, as determined by one-way ANOVA and Post-hoc tests. This study demonstrates that positive interference; caused by silica clot activator and silicone surfactant of the collection tubes; increases measured concentration of lithium. This interference; being in the pre-analytic phase, cannot be detected by routinely performed laboratory quality control. Bangladesh J Med Biochem 2015; 8(2): 60-65